Treatment outcomes of patients with acinetobacter infection : comparison between polymyxin versus non polymyxin based therapy - Jeeawoody, Aakil (2019)
Background: The growing resistance of Acinetobacter to almost all commercially available antibiotics is of major concern. Limited therapeutic options are currently available. Objectives: The aim of the study was to compare the efficacy of sulbactam regime to that of polymyxin B in the treatment Acinetobacter infection. Methods: This was a retrospective study of case records over one year period (1st January 2018 to 31st December 2018) at the Hospital Universiti Sains Malaysia. Patients of least 18 years old, with clinical and microbiological evidence of Acinetobacter infection, were enrolled in the study. Results: 34 patients received polymyxin and 38 received either ampicillin-sulbactam or cefoperazone-sulbactam. 24 (63.2%) from the nonpolymyxin group achieved clinical success while 13 (38.2%) achieved clinical success in the polymyxin group. 26 patients (68.4%) treated with nonpolymyxin achieved microbiological success compared to 18 (52.9%) treated with polymyxin. Mortality was lower in the nonpolymyxin group with 17 deaths (44.7%) compared to 23 deaths (67.6%) in the polymyxin group. Multiple logistic regression showed that microbiological failure was significantly associated with 30 days in patient mortality. Conclusion: The most important finding of our study is that sulbactam appears to have a better efficacy compared to polymyxin in treating Acinetobacter infection.